How Much "Group" is there in Online Group Work? - Lowes, Susan (Online Learning, 2014)
The ability to work in groups across time and space has become a frequent requirement for the workplace and is increasingly common in higher education, but there is a surprising lack of research on how online groups work. This research applies analytic approaches used in studies of face-to-face classroom “talk” to multiple groups in two online high school courses. We found two activities that demanded group problem-solving styles—one for deciding how to work as a group and a second for responding to the content of the assignment; that successful groups had directive leaders; and that most groups divided the labor, working in parallel rather than collaboratively.